A route toward high-detectivity and low-cost short-wave infrared photodetection: GeSn/Ge multiple-quantum-well photodetectors with a dielectric nanohole array metasurface - Chen, Qimiao (2023)
High-detectivity and low-cost short-wave infrared photodetectors with complementary metal−oxide−semiconductor (CMOS) compatibility are attractive for various applications such as next-generation optical communication, LiDAR, and molecular sensing. Here, GeSn/Ge multiple-quantum-well (MQW) photo-detectors with a dielectric nanohole array metasurface were proposed to realize high-detectivity and low-cost SWIR photodetection. The Ge nanohole array metasurface was utilized to enhance the light absorption in the GeSn/Ge MQW active layer. Compared with metallic nanostructures, the dielectric nanohole structure has the advantages of low intrinsic loss and CMOS compatibility. The introduction of metasurface architecture facilitates a 10.5 times enhanced responsivity of 0.232 A/W at 2 μm wavelength while slightly sacrificing the dark current density. Besides, the metasurface GeSn/Ge MQW photodetectors benefit 35% improvement in the 3 dB bandwidth compared to control GeSn/Ge MQW photodetectors, which can be attributed to the reduced RC delay. Due to the high responsivity and low dark current density, the room temperature specific detectivity at 2 μm is as high as 5.34 × 109 cm·Hz1/2/W, which is the highest among GeSn photodetectors and is better than commercial InSb and PbSe photodetectors operating at the similar wavelength. This work offers a promising approach for achieving low-cost and effective photodetection at 2 μm, contributing to the development of the 2 μm communication band.